What does RCEP mean for insiders and outsiders? The experience of India and Sri Lanka - Ganeshan Wignaraja (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2018)
This paper explores the economic implications of the Regional Comprehensive Economic Partnership (RCEP) - Asia's largest trade agreement - on India and Sri Lanka. The findings from existing model-based studies suggest that India, as an insider economy, will potentially gain from the RCEP while outsider economy Sri Lanka will likely loose. India faces challenges in the RCEP negotiations in liberalizing goods and services trade and adopting new intellectual property rules. Building business competitiveness and policy reforms can mitigate these challenges. Sri Lanka is banking on its recent FTA with Singapore as a stepping stone to the RCEP. But both Singapore and Sri Lanka need to do more to ensure that the benefits flow to Sri Lanka. Key issues include Singaporean support for Sri Lanka to join the RCEP, increasing ASEAN FDI to Sri Lanka, addressing the bilateral trade deficit and improving stakeholder consultations on FTAs in Sri Lanka.
Keywords: F14; F15; F17; 330; Free Trade Agreements; The RCEP; India; Sri Lanka